Geospatial Mapping and Health Status of Some Important Ornamental Fish Habitats of Upper Assam, India - Deb, Shatabdi; Nayak, Nipen; Biswas, Shyama Prasad (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
To conserve and manage water resources, it is crucial to create a record of water bodies and their catchments, which can be accomplished through digitized maps. The research focused on five rivers - River Dibru, River Sessa, River Burhidihing, River Brahmaputra, as well as two wetlands of Upper Assam - Maguri Beel, and Mer Beel. These water bodies were chosen based on their abundant fishery resources. Each selected water body was divided into three segments, and one sampling station from each segment was selected for monitoring water quality and recording fish species. The distribution of the catchment area was analyzed in the form of raster maps and geomorphology maps. Based on fish landings, the water bodies were identified and classified, and fish samples were collected through regular field surveys. Over the period from January 2021 to December 2022, eleven physicochemical parameters of the selected water bodies were recorded seasonally to assess the health status of each water bodies. Similarly, the health status and growth coefficient of each fish specimen was done. Water parameters were mostly within the standard limits and demonstrated only a narrow range of seasonal variation. In the studied water bodies, 49 ornamental fish species representing 32 genera under 18 families and 8 orders were found. Among the water bodies, River Dibru had the highest number of ornamental fish species at 46. The order Cypriniformes was dominant in all the studied sites.